Amazing animals of Australia. (Washington, D.C. : National Geographic Society, 1984)
Describes the kangaroo, platypus, and other animals native to Australia and discusses their origin and adaptation to their environment.
Includes index.
Bibliography: p. 103.
Keywords: Animals -- Australia -- Juvenile literature; Animals -- Australia